1995
DOI: 10.1295/polymj.27.141
|View full text |Cite
|
Sign up to set email alerts
|

Chiroptical Properties of Oligomers of m-Methylphenyl Isocyanate Bearing an Optically Active End-Group

Abstract: ABSTRACT:Oligomerization of m-methylphenyl isocyanate (mMePI) with lithium amide of (S)-( -)-2-(methoxymethyl)pyrrolidine (MMP) was carried out to obtain oligomers containing a chiral residue at the initial chain end (ix-end). The oligomers of degree of polymerization (DP) less than eighteen were separated in terms of DP and the specific rotation of each oligomer was estimated. The oligomers showed the high optical rotation which is ascribed to the structure prevailing in one-screw sense. The specific rotation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 10 publications
3
22
0
Order By: Relevance
“…The specific rotation of the oligomers of mMeOPI and 3,5MePI increased with an increase in DP in the range of DPs 13 and DPs 15, respectively. As described in the previous report, 11 this is probably because in these DP ranges the oligomers have no helix 102 reversal point and the helical structure becomes stiffer as the DP increases because the vicinity of polymer chain ends should have a higher mobility than the interior of a polymer chain and this effect of the chain ends should be reduced as the DP increases. The gradual decrease of the specific rotation in the higher DP range may be caused by the helix reversal in the main chain.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The specific rotation of the oligomers of mMeOPI and 3,5MePI increased with an increase in DP in the range of DPs 13 and DPs 15, respectively. As described in the previous report, 11 this is probably because in these DP ranges the oligomers have no helix 102 reversal point and the helical structure becomes stiffer as the DP increases because the vicinity of polymer chain ends should have a higher mobility than the interior of a polymer chain and this effect of the chain ends should be reduced as the DP increases. The gradual decrease of the specific rotation in the higher DP range may be caused by the helix reversal in the main chain.…”
Section: Resultsmentioning
confidence: 59%
“…We already reported that in the mMePI oligomers helix reversal starts from DP= 13. 11 From these results, it is clear that 3,5MePI oligomers which have an additional methyl group at the meta position of mMePI oligomers start to have helix reversals at higher DP than the mMePI oligomers; in other words, poly(3,5MePI) has a longer average persistence length of a helical structure than poly(mMePI). Both electronic and steric factors of the substituents introduced on the phenyl group may affect the persistence length of the helical structure of these oligomers.…”
Section: Resultsmentioning
confidence: 91%
“…Figure 9 shows a comparison between experiment and theory for chirally initiated poly(m-methylphenyl isocyanate) (PmMePI/Li-MMP). 27 In the panel (a), theoretical curves for different v values are drawn to approximately follow the data points by choosing appropriate values for [aJm(a-1)/(a+ 1). The data for N larger than 13 can be fitted accurately to the theory In the above treatment, [ocJm is defined as the specific rotation of monomer residue in a perfect helical conformation and is assumed not to depend on chain length.…”
Section: Analysis Of Experimental Datamentioning
confidence: 99%
“…The CD intensity of 2 depended on the molecular weight, and the polymer prepared in run 2 exhibited the largest intensity. Previously, Okamoto and coworkers52–55 reported similar observations for polymers prepared by the asymmetric polymerization of phenylisocyanate derivatives; they clarified that the persistence length of the helical structure was relatively short for the poly(phenyl isocyanate) bearing the chiral initiator residue in the terminal end and that the one‐handed helical sequences decreased with an increasing degree of polymerization. Therefore, polymer 2 should partially form a one‐handed helical structure, which was preserved by the chirality of MMP bonding to the terminal end in 2 .…”
Section: Resultsmentioning
confidence: 60%
“…The asymmetric polymerization using a chiral initiating system is extensively known as an effective approach to producing a one‐handed helical polymer, and this strategy has been applied to the preparations of a number of helical polymers 42–51. In fact, Okamoto and coworkers52–55 achieved the synthesis of a one‐handed helical polyisocyanate by means of this synthetic procedure. Thus, the asymmetric polymerization of phenylisocyanate bearing crown ether should be a suitable candidate for producing the one‐handed helical arrays of crown ether.…”
Section: Introductionmentioning
confidence: 99%